Evaluation of CD8+ response in QuantiFERON-TB Gold Plus as a marker of recent infection. (August 2021) - Viana Machado, Francisco; Morais, Clara; Santos, Sofia; Reis, Ricardo
Abstract: Background: Diagnosis and treatment of latent tuberculosis (TB) infection (LTBI) is essential for the elimination of TB. Preventive therapy could be limited to those with recent TB contact. QuantiFERON-TB Gold Plus (QFT-Plus), a new Interferon-γ release assay, includes a new antigen tube (TB2), which elicits CD4 + and CD8 + T-cell responses. Objective: The aim of the study was to evaluate CD8 + T-cell response as a marker of recent TB infection. Design: We retrospectively studied 1165 patients who were screened for LTBI. Patients were divided according to history of recent exposure to TB (contact with a confirmed index case in the previous year). CD8 + T-cell activity was measured as the difference between QFT-Plus tubes (TB2-TB1) using two cut-offs (>0.35 IU/mL and >0.60 IU/mL). Results: CD8 + T-cell activity was significantly higher in the exposed group for both cut-offs (96 - 13% vs 36 - 5% patients - OR 1.68, 95% CI 1.13–2.52 for >0.35 IU/mL and 77 vs 28 patients - OR 1.72 95% CI 1.10–2.70 for >0.60 IU/mL). CD8 + T-cell activity also showed an association with positive sputum smear of the index case and higher exposure time. Conclusion: CD8 + T-cell activity as measured with TB2-TB1 shows a significant association with recent exposure to TB, especially in patients with higher exposure and may prove to be a useful tool in identifying patients with recent LTBI. Highlights: Diagnosis and treatment of latent Tuberculosis infection is essential. QuantiFERON-TB Gold Plus provides surrogate markers of CD8 + T-cell responses. CD8+T-cell activity was associated with being a recent contact. CD8+T-cell IFNγ response was associated with smear grade of index and estimated exposure time.